Understanding institutional repository in higher learning institutions: a systematic literature review and directions for future research - Asadi, Shahla; Abdullah, Rusli; Jusoh, Yusmadi Yah; Nazir, Shah (Institute of Electrical and Electronics Engineers, 2019)
Institutional repositories (IRs) have received considerable attention from researchers across disciplines and around the globe. They have potentially increased the public value, ranking, prestige and visibility of researchers and relevant universities. However, despite the important and rapid growth of research in this area, few efforts have been made to systematically review and integrate the findings from previous research studies or to examine the current state of study regarding IRs. The primary goal of this paper is to provide a better understanding and an in-depth review of the current state of study regarding IRs. This research uses systematic literature review (SLR) and followed a protocol to properly organize the work related to institutional repositories. The data were collected from primary studies published from 2007 to 2018 from the six major databases (ScienceDirect, IEEE Explorer, Springer, ACM, Taylor and Francis and Emerald insight). Several papers regarding IRs were reviewed, applying inclusion and exclusion criteria, and a total of 115 studies were included as the main part of this research. The results obtained from these studies indicated that the absence of knowledge of open access IRs among scholars and institutions, and inadequate information and communication technology infrastructure were significant challenges behind the development of open access IRs. Meanwhile, enhanced visibility of the academic institution, increased local and global rankings, increased prestige and public value, and improved teaching, learning and research development by the scholars of the institution were found to be the main benefits of institutional repositories. This study also highlighted that most of the studies in this research area were focused on the "deployment, implementation and adoption" and "benefits and challenges" of institutional repositories. The outcomes of this study can assist future researchers by providing a roadmap of institutional repositories and highlighting guidelines for successful implementation of IRs in higher learning institutions.